2015
DOI: 10.5056/jnm15034
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation for Atrial Fibrillation Elicited “Jackhammer Esophagus”: A New Complication Due to Vagal Nerve Stimulation?

Abstract: Radiofrequency catheter ablation (RFCA) is a potentially curative method for treatment of highly symptomatic and drug-refractory atrial fibrillation (AF). However, this technique can provoke esophageal and nerve lesion, due to thermal injury. To our knowledge, there have been no reported cases of a newly described motor disorder, the Jackhammer esophagus (JE) after RFCA, independently of GERD. We report a case of JE diagnosed by high-resolution manometry (HRM), in whom esophageal symptoms developed 2 weeks aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
1
16
1
1
Order By: Relevance
“…However, the jackhammer phenotype is heterogenous, and exaggerated contraction has also been demonstrated in the context of distal obstruction, in esophageal submucosal infiltration with eosinophils, in opioid‐induced esophageal dysfunction, and in esophageal hypersensitivity with or without gastroesophageal reflux as a noxious trigger . Hypercontractile esophagus has also been reported after ablation therapy for atrial fibrillation, and after lung transplant, hypothesized to be related to irritation, stimulation or ablation of the vagus nerve. These associations lend credence to the notion that there might be an inherent predisposition toward esophageal hypercontractility in some individuals, and various mechanical, inflammatory, and luminal factors can trigger the manometric manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the jackhammer phenotype is heterogenous, and exaggerated contraction has also been demonstrated in the context of distal obstruction, in esophageal submucosal infiltration with eosinophils, in opioid‐induced esophageal dysfunction, and in esophageal hypersensitivity with or without gastroesophageal reflux as a noxious trigger . Hypercontractile esophagus has also been reported after ablation therapy for atrial fibrillation, and after lung transplant, hypothesized to be related to irritation, stimulation or ablation of the vagus nerve. These associations lend credence to the notion that there might be an inherent predisposition toward esophageal hypercontractility in some individuals, and various mechanical, inflammatory, and luminal factors can trigger the manometric manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…According to our review of the literature, this represents the first report of esophageal spasm after electrical cardioversion. Tolone et al described a case of jackhammer esophagus two weeks after catheter ablation for atrial fibrillation, assuming a radiofrequency-induced vagal nerve thermal injury as the provoking factor [4] . Khan and colleagues reported an episode of transient esophageal hypercontractility 4 weeks after lung transplantation, hypothesizing a vagotomy-related gastro-esophageal reflux disease as the causative mechanism [5] .…”
Section: Discussionmentioning
confidence: 99%
“…A case report has described jackhammer oesophagus noted in a postlung transplant patient, which later resolved 5. Similarly, Tolone et al 6 reported jackhammer oesophagus triggered by radiofrequency catheter ablation in a patient with atrial fibrillation. Eosinophilic oesophagitis with muscularis propria infiltration was recently reported in association of hypercontractile oesophagus in Japan,7 and was successfully treated with a peroral endoscopic myomectomy (POEM) procedure.…”
Section: Introductionmentioning
confidence: 94%